A New Species Nyctegretis seminigra sp. nov. (Pyralidae, Phycitinae) Revealed by Congruent Morphological and Mitogenomic Evidence - Linlin Yang; Yuxian Zhou; Yingdang Ren (Insects)
The genus Nyctegretis was established by Zeller [...]